Managerial ownership and financial performance: empirical evidence of the application of sharia principles in Indonesia - Heri Purnomo; Ulydhatul Ismiyana; Monika Bunga Richter (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - This study aims to examine the relationship between managerial ownership and financial performance through the aplication of sharia principles in Indonesia. Method - This study uses a financial report sample from 380 companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The estimation method used is Pooled OLS (CEM). We conducted the Durbin-Wu-Hausman (DWH) test to checking endogeneity issues. We also conduct a robustness test using Robust Least Square (RLS) to ensure the reability of our results. Result - The results of this study indicate that managerial ownership has a positive effect on financial performance through the aplication of sharia principles. We found that the principle of amanah (trustworthiness) and maslahah (public interest) ensures that managerial decision-making is not only for personal benefit but also for the interests of shareholders. Additionally, we found that the principle of ta’awun (mutual benefit) and 'adl (justice) ensures that every decision and action between managerial ownership and shareholders is based on balance. Implication - This study it highlights the need to formalize Sharia-based governance guidelines that limit excessive managerial ownership while mandating ethical decision-making transparency. For Islamic finance literature, it establishes Sharia Enterprise Theory as a viable extension of Sharia-based Agency Theory. Originality - We integrate the Islamic perspective into managerial ownership by incorporating fundamental Islamic principles of accountability.